A practical approach for synthesis of biodiesel via non-edible seeds oils using trimetallic based montmorillonite nano-catalyst. (May 2021) - Munir, Mamoona; Ahmad, Mushtaq; Mubashir, Muhammad; Asif, Saira; Waseem, Amir; Mukhtar, Ahmad; Saqib, Sidra; Siti Halimatul Munawaroh, Heli; Lam, Man Kee; Shiong Khoo, Kuan; Bokhari, Awais; Loke Show, Pau
Highlights: Novel trimetallic loaded with montmorillonite clay catalyst has been synthesized. Structural characterizations of developed catalyst has been done extensively. Optimization of non-edible Celastrus paniculatus Wild seed oil biodiesel synthesis. Catalyst exhibits high stability, activity and economic viability. Abstract: The potential of new trimetallic (Ce, Cu, La) loaded montmorillonite clay catalyst for synthesizing biodiesel using novel non-edible Celastrus paniculatus Willd seed oil via two-step transesterification reaction has been reported along with catalyst characterization. Transesterification reaction was optimized and maximum biodiesel yield of 89.42% achieved under optimal operating reaction states like; 1:12 oil to methanol ratio, 3.5% of catalyst amount, 120 °C of reaction temperature for 3 h. The predicted and experimental biodiesel yields under these reaction conditions were 89.42 and 89.40%, which showing less than 0.05% variation. Additionally, optimum biodiesel yield can be predicted by drawing 3D surface plots and 2D contour plots using MINITAB 17 software. For the characterization of the obtained biodiesel, analysis including the GC/MS, FT-IR, 1 H NMR and 13 C NMR were applied. The fuel properties of obtained biodiesel agrees well with the different European Union (EU-14214), China (GB/T 20828), and American (ASTM-951, 6751) standards.